Solving Exponential and Logarithmic Equation In exercise,solve for x or t.See example 5 and 6.
In x - In(x - 6) = 3

Respuesta :

Answer:

[tex]x=\frac{6e^3}{e^3-1}[/tex]

Step-by-step explanation:

[tex]ln x - ln(x - 6) = 3[/tex]

Apply natural log property

ln mn=ln m + ln(n), ln(m/n)=ln(m)-ln(n)

[tex]ln x - ln(x - 6) = 3[/tex]

[tex]ln(\frac{x}{x-6} )=3[/tex]

All natural log has base 'e'

[tex]\frac{x}{x-6} =e^3[/tex]

cross multiply

[tex]x=e^3(x-6)[/tex]

[tex]x=e^3x-6e^3[/tex]

add 6e^3 on both sides and -x on both sides

[tex]6e^3=e^3x-x[/tex]

[tex]6e^3=x(e^3-1)[/tex]

Divide e^3-1 on both sides

[tex]x=\frac{6e^3}{e^3-1}[/tex]